2005
DOI: 10.1136/gut.2003.032920
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of functional anti-YMDD and -mutant cytotoxic T lymphocytes after in vitro expansion correlates with successful response to lamivudine therapy for chronic hepatitis B

Abstract: Background: Many determinants for a sustained response to lamivudine therapy have been reported but the role of T cell responsiveness remains unclear. The finding that tyrosine-methionine-aspartate-aspartate (YMDD) motif of the reverse transcriptase domain of hepatitis B virus (HBV) DNA polymerase carries a HLA-A2 restricted cytotoxic T lymphocyte (CTL) epitope makes quantitative measurement of the numbers of peptide specific CTLs feasible using MHC tetramer-peptide complex staining. Aim: To investigate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Likewise, Figure 1b shows the prediction of 15-mer peptides of continuous amino acid sequences on HBcAg 1-30 using the SYFPEITHI scoring system on DRB1*0401 molecule correlates proliferation assays of CD4 + CD25 + T reg cells from DRB1*0401 patients in terms of [H 3 ] thymidine incorporation. The proliferation in response to peptide P16 (HBcAg [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] , with an SYFPEITHI score = 20 on DRB1*0401 molecule) was comparable to that of rHBcAg, thus this peptide (as P2 in Supplementary Table 1) was selected for the construction of DRB1*0401 tetramer in this study. These data of proliferation are consistent with reports that MHC class II tetramers may identify peptide-specific human CD4 + T cells proliferating to viral antigens [27,34], and with that T reg cell population could be induced and expanded by foreign antigen [35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, Figure 1b shows the prediction of 15-mer peptides of continuous amino acid sequences on HBcAg 1-30 using the SYFPEITHI scoring system on DRB1*0401 molecule correlates proliferation assays of CD4 + CD25 + T reg cells from DRB1*0401 patients in terms of [H 3 ] thymidine incorporation. The proliferation in response to peptide P16 (HBcAg [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] , with an SYFPEITHI score = 20 on DRB1*0401 molecule) was comparable to that of rHBcAg, thus this peptide (as P2 in Supplementary Table 1) was selected for the construction of DRB1*0401 tetramer in this study. These data of proliferation are consistent with reports that MHC class II tetramers may identify peptide-specific human CD4 + T cells proliferating to viral antigens [27,34], and with that T reg cell population could be induced and expanded by foreign antigen [35].…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids that are regarded as having a negative effect on the binding ability are given values between )1 and )3. The 17 peptides with 15-mer amino acids used in this study were arbitrarily designed (their SYFPEITHI scores not shown, Supplementary Table 1), of which, P2, LSFLPSDFFP SVRDL (HBcAg [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ) and P13, PPAYRPPNAPILSTL (HBcAg 129-143 ) had the highest SYFPEITHI scores, i.e., 20 and 28, for DRB1*0401 and DRB1*0101 molecules, respectively. They were used for the construction of each of MHC class II tetramers.…”
Section: Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference from our study may suggest that our patients were predominately Genotype C, in contrast to the European study, which mainly involved those of Genotype A or D. Another possibility may be the presence of fewer substitutions in the rt region at commencement of therapy, either alone or with emergence of YMDD mutant, as discussed below. A recent report showed that sustained lamivudine responders with HLA-A2 elicited more potent cytotoxic Tlymphocyte (CTL) immunity against YMDD and its mutant (YIDD and YVDD) [Lin et al, 2005]. Although we do not have HLA type data for the patients in our study, anti-mutant CTLs such as those described above may contribute in suppressing the elevation of mutant virus loads.…”
Section: Discussionmentioning
confidence: 77%